Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales - Poore, Gary C. B.; Dworschak, Peter C. (Zootaxa, 2017)
Re-examination of the holotype of Calliaxiopsis madagassa Sakai & Türkay, 2014 has led to the conclusion that the genus is a synonym of Calliaxina Ngoc-Ho, 2003 and the species is a senior synonym (by 6 months) of Calliaxina thomassini Ngoc-Ho, 2014, now Calliaxina madagassa (Sakai & Türkay, 2014). Both are from Madagascar. Comparison of the holotype of Tosacallianassa hatasagaensis Sakai, 2016 with several published figures of Ctenocheles balssi Kishinouye, 1926 has similarly found their genera and species synonymous. Further, the family Tosacallianassidae is synonymous with Ctenochelidae Mannning & Felder, 1991. Both species are from the same limited area in Japan. The nephropid species Thaumastochelopsis plantei Burukovsky, 2005 is transferred to Ctenocheles.